Optimization of stretching process for improve the textural characteristics of Kashar cheese - Çelebi, M; Şimşek, B (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was aimed to optimize the stretching process (temperature, titration acidity, and NaCl concentration) and to determine the subsequent effects over the quality characteristics of Kashar cheese. The textural and meltability properties were studied in the optimization. Whey was used to set the acidity of stretching water. Textural, meltability, and sensory evaluation scores of matured Kashar cheese obtained from the marketplaces were used for target values ​​to optimize the stretching process. The response surface methodology was used to optimize conditions for stretching process, the arrangement of experimental design and evaluation of analysis results. The optimum conditions were found as follows: 80.20 °C for stretching temperature; 0.61 °SH for stretching water acidity; and 12.00 % for NaCl concentration. Under these conditions: 79.53 N for hardness, -292.24 g.sec for adhesiveness, 0.74 for cohesiveness, 51.20 N for gumminess, and 19.05 mm for meltability values were found in Kashar cheese that was produced for validation. The validation production results were within 95 % confidence intervals for each response obtained at optimal conditions. Thus, this model is successful to predict the textural and meltability values ​​of sample.